(untitled) (Hematology Meeting Reports, 2009)
Of 121 mini transplants carried out altogether in Non Hodgkin’s lymphoma by our group and associates, 50 had been in high grade Non Hodgkin’s lymphoma with 16 of those in patients previously transformed. 21 have been in mantle cell lymphoma and 50 have been in follicular lymphoma. It is this last group pf 50 in follicular lymphoma that will be described in this presentation.